Chi Spacca : a new approach to American cooking - Silverton, Nancy; Carreño, Carrolynn; DeNicola, Ryan (Alfred A. Knopf, 2020)
"Recipes from the meat-centric menu at Chi Spacca, Nancy Silverton's Los Angeles steakhouse"--